A Study to Analyse the Perception of Commuters' towards Service Quality of Delhi Metro Rail Corporation: Empirical Study - Mukesh Singh, Yogendra Pal Bharadwaj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In modern era of globalization, the services being offered by the public transportation require to gauge sensitivity about the services offered to the common masses. In this context, this study examined the perception of commuters on service quality offered by Delhi Metro Rail Corporation and its impact on the commuter’s satisfaction. Therefore, five dimensions of service quality have been taken (reliability, tangibility, empathy, safety & security, commuters’ friendliness) as predicting variables towards the commuters’ satisfaction of DMRC. This research was carried out on behalf of a convenience sampling approach using basic condition and structural equation modelling with an aggregate of 1045 questionnaires distributed among commuters via electronic form as well as simple form. The results of factual tests show that four out of five predictive variables viz., commuters’ friendliness, tangibility, safety & security, empathy have pragmatic percussion, while reliability and commuter’s friendliness has no remarkable influence on customer’s satisfaction.